2019
DOI: 10.1111/ajt.15284
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of deceased solid organ donors and screening results for hepatitis B, C, and human immunodeficiency viruses — United States, 2010–2017

Abstract: This report summarizes the increasing use of increased‐risk deceased organ donors, noting the association of HCV and HBV with this designation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Given the rise of HCV Ab+ donors in the United States based on available national data, the addition of DAA agents to our therapeutic arsenal has allowed us to explore the utilization of these increased risk organs . The transplant community underwent a similar transformation for hepatitis B core antibody positive liver grafts in the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rise of HCV Ab+ donors in the United States based on available national data, the addition of DAA agents to our therapeutic arsenal has allowed us to explore the utilization of these increased risk organs . The transplant community underwent a similar transformation for hepatitis B core antibody positive liver grafts in the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 0.2% had a positive HIV antibody, 0.7% had a positive HBV surface antigen, 7.5% had a positive HBV core antibody, and 7.3% had a positive HCV antibody result. These rates are significantly higher than those from actual deceased organ donors: 0% HIV Ab, 0.1% HBsAg, 4.8% HBcAb, and 5.3% HCV Ab ( P < .0001) 20…”
Section: Discussionmentioning
confidence: 70%
“…Donors with one or more risk factors are designated as increased risk donors (IRDs) per these recommendations. Due largely to the current US opioid crisis, a growing number and proportion of organ donors are IRDs, increasing from 8.9% in 2010 to 26.3% in 2017 12 . Because HHV‐8 infection shares risk factors with HIV, HBV, and HCV infection, increasing numbers of IRD may elevate the risk of donor‐derived HHV‐8 and development of KS.…”
Section: Introductionmentioning
confidence: 99%